Development of the venom delivery system in Elapidae snake species: Naja siamensis and Oxyuranus microlepidotus. (August 2021) - Logan, Jessica M.; Beck, Andrew; Dunstan, Nathan; Allen, Luke; Woods, Anthony E.
Abstract: Many advanced snakes possess a unique venom delivery system which they utilise to subdue prey and for defence. Despite extensive efforts, the evolutionary differences in this key system between advanced snake families remains enigmatic. The current study has investigated the development of the venom delivery system using two oviparous Elapidae models, Naja siamensis and Oxyuranus microlepidotus . The development stages of the embryos in both models were detailed using previously standardised characterisation. Variations in the days post-oviposition between these stages was observed, despite a continuous development trajectory. These differences also translated to the development of the venom delivery system. Highlights: Characterisation of embryonic development of Naja siamensis and Oxyuranus microlepidotus species. Variations in the days post-oviposition between development stages observed, despite a continuous development trajectory. Embryonic venom delivery system described throughout development. Accessory gland not identified during embryonic development of either species.